2020
DOI: 10.1038/s42255-020-00316-0
|View full text |Cite
|
Sign up to set email alerts
|

The hexosamine biosynthesis pathway is a targetable liability in KRAS/LKB1 mutant lung cancer

Abstract: In non–small cell lung cancer (NSCLC), concurrent mutations in the oncogene KRAS and the tumor suppressor STK11 encoding the kinase LKB1 result in aggressive tumors prone to metastasis but with liabilities arising from reprogrammed metabolism. We previously demonstrated perturbed nitrogen metabolism and addiction to an unconventional pathway of pyrimidine synthesis in KRAS/LKB1 co-mutant (KL) cancer cells. To gain broader insight into metabolic reprogramming in NSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 50 publications
4
97
0
Order By: Relevance
“…UTP is critical for protein glycosylation by serving as a glycosylation substrate sub-fraction. It is reported that protein glycosylation level is generally elevated in various malignancies and has been identified as a hallmark of cancer (61). As an abundant post-translational modification of protein, glycosylation takes part in sustaining cancer cell growth and proliferation (62)(63)(64)(65)(66)(67)(68)(69).…”
Section: Dysfunction Of Pyrimidine Metabolism In Cancersmentioning
confidence: 99%
“…UTP is critical for protein glycosylation by serving as a glycosylation substrate sub-fraction. It is reported that protein glycosylation level is generally elevated in various malignancies and has been identified as a hallmark of cancer (61). As an abundant post-translational modification of protein, glycosylation takes part in sustaining cancer cell growth and proliferation (62)(63)(64)(65)(66)(67)(68)(69).…”
Section: Dysfunction Of Pyrimidine Metabolism In Cancersmentioning
confidence: 99%
“…Besides, transsulfuration‐mediated cysteine synthesis is critical for promoting tumour growth in vivo 38 . The hexosamine biosynthetic pathway is a shunt pathway of glycolysis and is a metabolic node in cancer cells 39 . Studies have shown that the up‐regulation of the hexosamine biosynthetic pathway is related to tumour survival and chemotherapy resistance 40 .…”
Section: Discussionmentioning
confidence: 99%
“… 38 The hexosamine biosynthetic pathway is a shunt pathway of glycolysis and is a metabolic node in cancer cells. 39 Studies have shown that the up‐regulation of the hexosamine biosynthetic pathway is related to tumour survival and chemotherapy resistance. 40 Inhibiting the biosynthetic pathway of hexosamine can have a significant therapeutic effect on patients with acute myeloid leukaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we need to evaluate how silibinin interacts with the BBB to impede transmigration of brain metastasisinitiating cells and/or to regulate the metabolism and brain accumulation of targeted therapies. The unraveling of an unforeseen, selective vulnerability of silibinin-treated tumor cells to the hexosamine biosynthesis pathway inhibitor azaserine using genomically edited isogenic models might exemplify how to exploit the therapeutic usage of silibinin in combination with certain targetable weaknesses in specific subtypes of lung cancer (e.g., KRAS/STK11 co-mutant tumors with dependence on the hexosamine biosynthesis pathway through GFPT2 [104]). Using silibinin as a lead structure to guide development, it would be possible to use synthetic chemistry approaches to generate a battery of silibinin derivatives with enhanced radiosensitizing capacity and augmented brain targeting.…”
Section: Silibinin and Lung Cancer: The Past Present And Future (A Corollary)mentioning
confidence: 99%